Carbon implications of converting cropland to bioenergy crops or forest for climate mitigation: a global assessment. Issue 1 (6th February 2015) - Albanito, Fabrizio; Beringer, Tim; Corstanje, Ronald; Poulter, Benjamin; Stephenson, Anna; Zawadzka, Joanna; Smith, Pete
Abstract: The potential for climate change mitigation by bioenergy crops and terrestrial carbon sinks has been the object of intensive research in the past decade. There has been much debate about whether energy crops used to offset fossil fuel use, or carbon sequestration in forests, would provide the best climate mitigation benefit. Most current food cropland is unlikely to be used for bioenergy, but in many regions of the world, a proportion of cropland is being abandoned, particularly marginal croplands, and some of this land is now being used for bioenergy. In this study, we assess the consequences of land‐use change on cropland. We first identify areas where cropland is so productive that it may never be converted and assess the potential of the remaining cropland to mitigate climate change by identifying which alternative land use provides the best climate benefit: C4 grass bioenergy crops, coppiced woody energy crops or allowing forest regrowth to create a carbon sink. We do not present this as a scenario of land‐use change – we simply assess the best option in any given global location should a land‐use change occur. To do this, we use global biomass potential studies based on food crop productivity, forest inventory data and dynamic global vegetation models to provide, for the first time, a global comparison of the climate change implications of either deploying bioenergy crops or allowing forest regeneration on current crop land, over a period of 20 years starting in the nominal year of 2000 ad . Globally, the extent of cropland on which conversion to energy crops or forest would result in a net carbon loss, and therefore likely always to remain as cropland, was estimated to be about 420.1 Mha, or 35.6% of the total cropland in Africa, 40.3% in Asia and Russia Federation, 30.8% in Europe‐25, 48.4% in North America, 13.7% in South America and 58.5% in Oceania. Fast growing C4 grasses such as Miscanthus and switch‐grass cultivars are the bioenergy feedstock with the highest climate mitigation potential. Fast growing C4 grasses such as Miscanthus and switch‐grass cultivars provide the best climate mitigation option on ≈485 Mha of cropland worldwide with ~42% of this land characterized by a terrain slope equal or above 20%. If that land‐use change did occur, it would displace ≈58.1 Pg fossil fuel C equivalent (Ceq oil). Woody energy crops such as poplar, willow and Eucalyptus species would be the best option on only 2.4% (≈26.3 Mha) of current cropland, and if this land‐use change occurred, it would displace ≈0.9 Pg Ceq oil. Allowing cropland to revert to forest would be the best climate mitigation option on ≈17% of current cropland (≈184.5 Mha), and if this land‐use change occurred, it would sequester ≈5.8 Pg C in biomass in the 20‐year‐old forest and ≈2.7 Pg C in soil. This study is spatially explicit, so also serves to identify the regional differences in the efficacy of different climate mitigation options, informing policymakers developing regionally or nationally appropriate mitigation actions.